The Concept of Developing Banyu Kencono Confluence Tourism Area as an Alternative of Economic Improvement for Bantul Regency Society - Nany Noor Kurniyati; Wulan Dari (Jurnal Mantik, 2022)
Managing tourism areas as to improve the society’s economy is an effort to activate the potential and integrate the surrounding society to get benefit from managing the tourism area. Natural potential possessed by the area can be used as an opportunity for the surrounding society in improving and developing tourism area to increase the income of the surrounding society. This research examined how the concept of developing Banyu Kencono Confluence tourism area as an alternative effort to support economic improvement of the surrounding society. The aim of this research is to be able to describe the potential of Banyu Kencono Confluence tourism area which can be developed and be able to construct a concept of developing the tourism area. Determination of factors supporting the development of Banyu Kencono Confluence tourism area and formulation of the concept of regional development have been done in this research. It is expected that the concept of developing a tourism area can improve the economy of the surrounding society. This research used descriptive research method with a qualitative approach. Data sources used were primary and secondary data. The data was collected using observation, interview and documentation techniques. The data analysis technique is in the form of qualitative descriptive analysis.